Cost Effective, ex situ Conservation (Air Layering) of Elaeocarpus Blascoi - an Endangered Medicinal Tree in Western Ghats of Palni Hills, Tamilnadu, South India - Pavendan, P.; Gideon, V. Anand; Sebastian Rajasekaran, C. (Indian Forester, 2012)
An air layering trial was conducted in Elaeocarpus blascoi Weibel during the pre monsoon season in the months of mid - march to mid - June, 2011 in Vattakanal Conservation Trust Nursery, Kodaikanal in Tamilnadu, South India. Lateral branches were girdled, and IBA 500, 750 and 1000 ppm was applied at the exposed surfaces and wrapped with moistened Sawdust. Rooting was responded after 60 days. The maximum rooting length (7.5 cm) was recorded with 1000 ppm IBA and the minimum rooting length (3.5 cm) was recorded with 500 ppm IBA and the control shoots failed to form roots (0.00 cm). Pre monsoon season (mid - march to mid - June) seems to be the best period for air layering in Elaeocarpus blascoi. A cost effective packaging system was worked out and deployed during this experimental trial.